Pengaruh terapi finger hold terhadap penurunan intensitas nyeri pada pasien dengan gangguan rasa nyaman nyeri post op fraktur tangan - Yusuf, Dody Iqbal; Chrisanto, Eka Yudha; Andoko, Andoko (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Fractures are a common health problem caused by trauma, particularly traffic accidents. Post-operative hand fracture patients commonly experience pain, which, if not properly managed, can interfere with the healing process. Pain management still focuses largely on analgesic medications, while non-pharmacological therapies such as finger holds can be an alternative. Purpose: To determine the effect of finger hold therapy on reducing pain intensity in post-operative hand fracture patients. Method: This quantitative study used a quasi-experimental one-group pretest and posttest design. A sample of 30 respondents was selected using purposive sampling technique according to inclusion criteria. The research instruments used an observation sheet and a Numeric Rating Scale (NRS). Data were analyzed using univariate and bivariate methods using the dependent t-test. Results: The mean and SD of pain intensity before intervention was 6.17 ± 1.020, while after finger hold therapy it decreased to 3.70 ± 1.643. The dependent t-test showed a p-value = 0.000 (p < 0.05), indicating a significant difference in pain intensity before and after the intervention. Conclusion: Finger hold therapy is effective in reducing pain intensity in post-operative hand fracture patients. This study suggests that finger hold therapy may be applied as a non-pharmacological intervention alongside analgesics in hospital pain management. Results: The average pain intensity before finger-hold therapy was 6.17±1.020, and after the therapy, it decreased to 3.70±1.643. The dependent t-test yielded a p-value of 0.000<0.05, indicating a significant difference in pain intensity before and after the intervention. Conclusion: Finger-hold therapy is effective in reducing pain intensity in post-hand fracture surgery patients. Therefore, it is recommended that finger-hold therapy be used as a non-pharmacological intervention alongside analgesics in pain management in hospitals. Keywords: Finger-hold; Fracture; Pain Intensity; Post-Operative. Pendahuluan: Fraktur merupakan masalah kesehatan yang banyak terjadi akibat trauma, khususnya kecelakaan lalu lintas. Pasien post operasi fraktur tangan umumnya mengalami nyeri yang jika tidak ditangani dengan baik dapat mengganggu proses penyembuhan. Penanganan nyeri masih banyak berfokus pada obat analgesik, sementara terapi non-farmakologis seperti finger hold dapat menjadi alternatif. Tujuan: Untuk mengetahui pengaruh terapi finger hold terhadap penurunan intensitas nyeri pada pasien post operasi fraktur tangan. Metode: Penelitian kuantitatif dengan desain quasi experimental one group pretest and posttest design. Sampel berjumlah 30 responden yang dipilih dengan teknik purposive sampling sesuai kriteria inklusi. Instrumen penelitian menggunakan lembar observasi dan Numeric Rating Scale (NRS). Analisis data dilakukan secara univariat dan bivariat dengan uji t-dependen. Hasil: Nilai rata-rata intensitas nyeri sebelum diberikan terapi finger hold adalah 6.17±1.020 dan setelah diberikan terapi menurun menjadi 3.70±1.643. Hasil uji t-dependen diperoleh p-value 0.000<0.05 yang menunjukkan terdapat perbedaan signifikan intensitas nyeri sebelum dan sesudah intervensi. Simpulan: Terapi finger hold berpengaruh dalam menurunkan intensitas nyeri pada pasien post operasi fraktur tangan sehingga disarankan agar terapi finger hold dapat dijadikan intervensi non-farmakologis pendamping analgesik dalam manajemen nyeri di rumah sakit. Kata Kunci : Fraktur; Finger Hold; Intensitas Nyeri; Post Operasi.